Crystal structures of VIM‐1 complexes explain active site heterogeneity in VIM‐class metallo‐β‐lactamases. (23rd November 2018) - Salimraj, Ramya; Hinchliffe, Philip; Kosmopoulou, Magda; Tyrrell, Jonathan M.; Brem, Jürgen; van Berkel, Sander S.; Verma, Anil; Owens, Raymond J.; McDonough, Michael A.; Walsh, Timothy R.; Schofield, Christopher J.; Spencer, James
Abstract : Metallo‐β‐Lactamases (MBLs) protect bacteria from almost all β‐lactam antibiotics. Verona integron‐encoded MBL (VIM) enzymes are among the most clinically important MBLs, with VIM‐1 increasing in carbapenem‐resistant Enterobacteriaceae ( Escherichia coli, Klebsiella pneumoniae ) that are among the hardest bacterial pathogens to treat. VIM enzymes display sequence variation at residues (224 and 228) that in related MBLs are conserved and participate in substrate binding. How they accommodate this variability, while retaining catalytic efficiency against a broad substrate range, has remained unclear. Here, we present crystal structures of VIM‐1 and its complexes with a substrate‐mimicking thioenolate inhibitor, ML302F, that restores meropenem activity against a range of VIM‐1 producing clinical strains, and the hydrolysed product of the carbapenem meropenem. Comparison of these two structures identifies a water‐mediated hydrogen bond, between the carboxylate group of substrate/inhibitor and the backbone carbonyl of the active site zinc ligand Cys221, that is common to both complexes. Structural comparisons show that the responsible Cys221‐bound water is observed in all known VIM structures, participates in carboxylate binding with other inhibitor classes, and thus effectively replicates the role of the conserved Lys224 in analogous complexes with other MBLs. These results provide a mechanism for substrate binding that permits the variation at positions 224 and 228 that is a hallmark of VIM MBLs. Enzymes: EC 3.5.2.6 Databases: Co‐ordinates and structure factors for protein structures described in this manuscript have been deposited in the Protein Data Bank (www.rcsb.org/pdb ) with accession codes5N5G (VIM‐1), 5N5H (VIM‐1:ML302F complex) and5N5I (VIM‐1‐hydrolysed meropenem complex). Abstract : The VIM metallo‐β‐lactamases protect bacteria from most β‐lactam antibiotics while escaping clinical inhibitors, but vary at residues (224, 228) interacting with substrate in related enzymes. Structures of VIM‐1 complexes with hydrolysed meropenem (carbapenem antibiotic) and a thioenolate inhibitor identify hydrogen bonding, via a conserved water molecule (Wat3), that enables retention of activity despite sequence variation at apparently essential residues.